Enzymes in farm animal nutrition - Bedford, M. R.; Bedford, M. R.; Partridge, G. G.; Partridge, G. G. (Wallingford :CABI Publishing, 2000)
This book contains 16 chapters by individual authors reviewing feed enzymes within the context of their mode of action, interaction with intestinal physiology, economic and environmental impacts, and application of the technology to the diets of various livestock species.
Fakulti Perubatan Veterinar
Keywords: LL500 - Animal Nutrition (General); RR130 - Feed Additives